2018
DOI: 10.1172/jci.insight.94952
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota modulates adoptive cell therapy via CD8α dendritic cells and IL-12

Abstract: Adoptive T cell therapy (ACT) is a promising new modality for malignancies. Here, we report that adoptive T cell efficacy in tumor-bearing mice is significantly affected by differences in the native composition of the gut microbiome or treatment with antibiotics, or by heterologous fecal transfer. Depletion of bacteria with vancomycin decreased the rate of tumor growth in mice from The Jackson Laboratory receiving ACT, whereas treatment with neomycin and metronidazole had no effect, indicating the role of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 76 publications
5
104
1
Order By: Relevance
“…105 Besides, additional vancomycin administration remarkably increased the abundance and activity of tumor-specific TIL. 105 This transformation to hot tumor was attributed to accumulated CD8α + DC and IL-12 in peripheral circulation, as well as concurrent enhanced Th1-skewed immune response. 105…”
Section: Manipulating Gut Microbiota To Enhance Effect Of Actmentioning
confidence: 99%
“…105 Besides, additional vancomycin administration remarkably increased the abundance and activity of tumor-specific TIL. 105 This transformation to hot tumor was attributed to accumulated CD8α + DC and IL-12 in peripheral circulation, as well as concurrent enhanced Th1-skewed immune response. 105…”
Section: Manipulating Gut Microbiota To Enhance Effect Of Actmentioning
confidence: 99%
“…This effect is dependent on G protein–coupled receptor 41 (GPR41, also called free fatty acid receptor 3 or FFAR3), but not GPR43 (also called free fatty acid receptor 2 or FFAR2) . DCs can also exert roles in adoptive T‐cell therapy (ACT) in cancer (Figure E), and the composition of the gut microbiome or treatment with antibiotics could lead to an increase in CD8α + DCs, and consequent IL‐12 release that sustains the anti‐tumor ACT …”
Section: Microbiota Regulating Cellular Players In Innate and Adaptivmentioning
confidence: 99%
“…E, The efficacy of adoptive T‐cell therapy was proven to be associated with the microbiome. The success of adoptive T‐cell therapy correlates with a peripheral increase and a more abundant tumor infiltration of CD 8α + DC producing IL ‐12 . Mouse treatment with SCFA results in the recruitment of bone marrow‐derived DC with impaired capacity to induce Th2 responses in the lung .…”
Section: Translational Implications Of Microbiotamentioning
confidence: 99%
“…More clinical data with longterm follow-up will be required to assess the longterm benefit of CAR T cells. 126 Further, the TME is highly immunosuppressive in solid tumors, 127 and hence, combination strategies that can alleviate the immunosuppressive environment will be important to test in future clinical trials. 5 Several factors could potentially have an impact on CAR Tcell efficacy, including the variable potencies of the CARs themselves.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A recent study demonstrated that the efficacy of adoptive therapy in a mouse model was significantly affected by differences in the composition of gut bacteria. 126 Further, the TME is highly immunosuppressive in solid tumors, 127 and hence, combination strategies that can alleviate the immunosuppressive environment will be important to test in future clinical trials.…”
Section: Future Perspectivesmentioning
confidence: 99%